Respuesta :

Answer:

The answer is 3x+2

Step-by-step explanation:

2(3x-1)-3x+4

I did distributive property on 2(3x-1) how I did that was I multiplied 2 times 3x which is 6x (2 times 3x=6x). Then I multiplied 2 times -1 which equals -2          (2 times -1=-2).

new expression:

6x-2-3x+4

I combined all the numbers with the variables (6x and -3x) and by subtracting both of them you get 3x (6x-3x=3x). After that you combine -2 and 4 which equals 2 (-2+4=2).

This is now the final expression (your answer):

3x+2

ACCESS MORE